Development aid and employment - Rolph van der Hoeven (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Globalization has led to a precarization of labour, which especially manifests in the unstable working conditions, a lower labour share in national income as well as in a growing income inequality, with the exception of some countries with high initial income inequality. The neglect of concern for employment and inequality in the formulation of the Millennium Development Goals (MDGs) in 2000 is noted; the addition of a goal for full employment in a reformulation of the MDGs in 2005 did not lead to a change in focus in official development assistance (ODA). If the growing concern for employment and inequality is taken seriously, a refocus of development efforts is necessary, combining a greater share of development assistance for employment and productivity enhancing activities with a change in national and international economic and financial policies, so as to make employment creation (together with poverty reduction) an overarching goal.
Keywords: J21; J38; O15; O19; 330; employment; inequality; development assistance; development goals; Erwerbstätigkeit; Ungeschützte Beschäftigung; Einkommensverteilung; Entwicklungshilfe